Bioprospecção de atividade antioxidante e antimicrobiana da casca de Stryphnodendron adstringens (Mart.) Coville (Leguminosae-Mimosoidae) - De Souza, Tatiana Maria [UNESP]; Severi, J. A. [UNESP]; Silva, V. Y. A. [UNESP]; Santos, E. [UNESP]; Pietro, R. C. L. R. [UNESP] (My University, 2007)
The aim of this work was to evaluate the class of secondary metabolites responsible for the antioxidant and antimicrobial activities of bark extracts of Stryphnodendron adstringens (Mart.) Coville (Leguminosae-Mimosoidae), a plant widely used in folk medicine in Brazil. Extracts of the bark were prepared with 50% ethanol, 70% ethanol, acetone:water (7:3, v/v) and chloroform. Antioxidant activity was prospected by spraying thin-layer chromatographs of the extracts with 2,2-diphenyl-1-picryl-hydrazyl (DPPH) and measuring the DPPH radical scavenging capacity by spectrophotometry. Antibacterial activity was revealed by the agar diffusion method and bioautography. TLC spots assigned to tannins in the polar extracts showed antioxidant activity by DPPH radical scavenging and the chloroform extract showed the least scavenging activity. Antimicrobial activity was indicated by the bacterial growth inhibition haloes around polar extracts and bioautography showed activity in the TLC spots assigned to tannins. It was concluded that polar extracts of the bark of S. adstringens possessed antioxidant and antimicrobial activities which were due to secondary metabolite derived from the tannin class, which are the main constituent of these bark extracts, according to the literature.

O presente estudo teve por objetivo avaliar a classe de metabólitos secundários responsável pela atividade antioxidante e antimicrobiana de extratos da casca de Stryphnodendron adstringens (Mart.) Coville (Leguminosae-Mimosoidae), planta amplamente utilizada medicinalmente pela população. Foram obtidos extratos da casca utilizando etanol 50%, etanol 70%, acetona:água (7:3, v/v) e clorofórmio. A bioprospecção da atividade antioxidante foi realizada por meio de cromatografia em camada delgada revelada com 2,2-difenil-1-picrilhidrazila (DPPH) e a capacidade de seqüestro de radicais livres utilizando DPPH foi quantificada por espectrofotometria. A bioprospecção da atividade antibacteriana foi realizada por meio de difusão em ágar e bioautografia. A cromatografia revelada com DPPH revelou atividade antioxidante na região onde foram identificadas as manchas referentes aos derivados de taninos e o extrato clorofórmico foi o que apresentou menor capacidade de seqüestro de radicais livres. A atividade antimicrobiana foi comprovada para os extratos polares pela formação de halos de inibição de crescimento bacteriano e a bioautografia revelou atividade na região onde foram identificadas as manchas de derivados tânicos. Assim, foi determinado que extratos da casca de S. adstringens apresentaram atividades antioxidante e antimicrobiana devido aos metabólitos secundários derivados da classe de taninos, que são os principais constituintes desta droga vegetal, de acordo com a literatura. Palavras-chave: Stryphnodendron adstringens; atividade antioxidante; atividade antimicrobiana; taninos.
Bioprospection of antioxidant and antimicrobial activities in the bark of Stryphnodendron adstringens (Mart.) Coville (Leguminosae-Mimosoidae)
Keywords: Antimicrobial activity; Antioxidant activity; Stryphnodendron adstringens; Tannins; 1,1 diphenyl 2 picrylhydrazyl; acetone; agar; alcohol; chloroform; drug metabolite; plant extract; Stryphnodendron adstringens extract; tannin; unclassified drug; water; agar diffusion; antibacterial activity; antimicrobial activity; antioxidant activity; bacterial growth; bark; bioautography; Brazil; comparative study; controlled study; drug isolation; drug screening; growth inhibition; legume; measurement; nonhuman; spectrophotometry; thin layer chromatography; traditional medicine